Challenges in speed and power development across age categories: a comparative study of female and male football players - Loturco, I.; Alcaraz, P. E.; Oliveira, L. P.; Tavares, L. D.; Requena, B.; Freitas, T. T.; Pereira, L. A. (Biology of Sport, 2025)
The popularity of women`s football has substantially increased over the last few decades. Despite this growing interest, few studies have compared the evolution of the physical performance of female football players across different age categories, and none have been conducted with players from the same club. Similarly, no studies have compared this progression between female and male players. We compared the evolution of speed-power qualities in female and male players from the same club throughout their specialization process, from the under-20 to the senior category. A total of 101 youth and senior female and male football players performed vertical jump, sprint speed, change-of-direction (COD) speed, and jump-squat power tests in this order, each conducted on separate occasions. Additionally, sprint momentum (SM) and COD-Deficit were also computed. Senior players demonstrated superior countermovement jump performance compared to under-20 players in both groups (ES = 0.86-0.93; P < 0.05). No significant differences were observed in squat jump and jump squat power between under-20 and senior players (P > 0.05). Similarly, no differences were found in any speed-related tests between under-20 and senior players in either group (P > 0.05). SM and COD-Deficit were similar across age categories for both sexes; however, SM was higher in men (ES = 2.05), while COD-Deficit was lower in female players (ES = 2.08; P < .001). In conclusion, men outperformed women in all physical tests, with smaller differences in speed-related performance (Difference = 14.2%). This gap was even narrower in more complex speed tasks, such as COD drills (Difference = 4.7%), and may be attributed to the significant difference in SM; greater in male players) and its impact on the COD-Deficit.